Predictors of blood pressure control among patients with hypertension: a cross-sectional study in a Nigerian tertiary health facility - Ugbe Maurice-Joel Ugbe; Ido Edem Ukpeh; Margaret Inemesit Akpan; Peter Bassey Enyievi; Nelson Chukwudi Osuchukwu; Ekpenyong Eyo Bassey; Smith Bakumor Yolo (BMJ Open)
Background Adequate blood pressure control improves clinical outcomes in patients with hypertension. Poor blood pressure control is linked with cardiovascular diseases and poor quality of life.Aim To identify the predictors of blood pressure control among patients with hypertension treated at the University of Calabar Teaching Hospital, Calabar, Nigeria.Methods This was a descriptive, cross-sectional study that recruited 441 hypertensive adults who were on medications for at least 6 months through systematic random sampling. Data were analysed using bivariate and multivariate methods at 95% CI and α=0.05. Blood pressure was measured twice using a mercury sphygmomanometer, with averages recorded.Results The average age of participants was 55.46 years±12.91. About 48.1% of respondents achieved adequate blood pressure control. Major reported risk factors of inadequate blood pressure control were sedentary lifestyle (67.8%), use of caffeinated drinks (51.9%) and family history of hypertension (47.5%). The major comorbidities of hypertension were gastrointestinal symptoms (46.72%) and diabetes (31.39%). The predictors of adequate blood pressure control were higher income (adjusted OR (AOR)=2.94, p=0.026), full health insurance (AOR=2.32, p=0.030), non-usage of caffeinated drinks (AOR=4.13, p=0.001) and normal body mass index (AOR=1.63, p=0.026). Predictors of inadequate blood pressure control were older age (AOR=0.30, p<0.001), living with a spouse (AOR=0.14, p=0.014), non-compliance with antihypertensive medications (AOR=0.53, p=0.040) and moderate obesity (AOR=0.29, p=0.032).Conclusion Addressing prevalent risk factors like sedentary lifestyle and dietary habits, as well as structural initiatives like accessibility to health insurance, presents opportunities for targeted interventions to enhance well-being and improve outcomes that will strengthen public health, clinical practice and research.